Politisasi Media di 2014: Aburizal Bakrie dan Segmen Pemilih Pemula - Rivai, Ardian Bakhtiar (Jurnal Politik Indonesia: Indonesian Political Science Review, 2016)
This paper investigates that influence of television for political behavior in Indonesian election on 2014. There is important to identify that televisions in Indonesia is a tool of capital to construct political perception of Indonesian citizens. Public resources information as television in Indonesia has not really objective, in addition there are the domination of media owner interesting for news information which is published. This paper focuses on understanding on young citizen segmentation whose have the high contribution for Indonesian election voters. Literature review and analytical are applied to the media domination model for support argumentation of highly influences of television in Indonesia. Based on explanation in this paper, we can understand that Indonesian election 2014 is not only about competition of candidate, it is clear that media owner competition.